Predictors Of Catastrophic Costs Of Tuberculosis (TB) Among Patients Co-Affected With TB-HIV And TB-Diabetes In Bhavnagar Region, Western India - Mihir Rupani; Sheetal Vyas (Medsci Publications, 2022)
Background: By the year 2030, no family with a patient of tuberculosis (TB) is supposed to incur catastrophic costs. In India, a significant number of people suffer from TB, and many face catastrophic costs. Our objective was to determine the predictors of catastrophic costs due to TB among co-prevalent TB-HIV and TB-diabetes patients. Methods: We conducted a cross-sectional study among 234 patients co-affected with TB-HIV and 304 patients with TB-diabetes co-prevalence in the Bhavnagar region (western part of India). TB costs, estimated using a validated questionnaire, were defined to be catastrophic when they exceeded 20% of annual household income. Multivariable logistic regression was used to determine the significant predictors of catastrophic costs of TB. Results: Four percent of patients in each group incurred catastrophic costs due to TB. Female gender [adjusted odds ratio aOR 6 (95% CI 1.2-33)], being single [aOR 9 (95% CI 1.5-52)], low socioeconomic status [aOR 7 (95% CI 1.2-30)], private consultation for TB [aOR 9 (95% CI 1.5-53)], and hospitalization in first HIV visit [aOR 19 (95% CI 3-137)] significantly predicted catastrophic costs of TB among patients co-affected with TB-HIV. Among patients with TB-diabetes co-prevalence, hospitalization in first TB visit [aOR 7 (95% CI 2-29)], and private consultation for TB [aOR 7 (95% CI 1.6-30)] were the significant predictors. Conclusions: Despite a lower percentage of TB-HIV/ TB-diabetes patients facing catastrophic costs, hospitalization and private care-seeking are the "modifiable" determinants of TB catastrophic costs in our study setting.